Emotion expression and intergroup bias reduction between Muslims and Christians: Long-term Internet contact. (December 2015) - White, Fiona A.; Abu-Rayya, Hisham M.; Bliuc, Ana-Maria; Faulkner, Nicholas
Highlights: Identifies how online emotion expression mediates contact and bias reduction. DIEC groups used more positive emotion and less anger and sadness words than controls. DIEC groups' reduced expressions of anger and sadness were related to reduced bias. Abstract: The Internet can play a critical role in improving intergroup relations. The current field experiment investigated how emotions expressed by participants in intergroup contact sessions—in the form of a synchronous online chat program—predicted a reduction in intergroup bias. Here 102 Muslim and 103 Christian high-school students spent eight Internet sessions in either a Dual Identity Electronic(E)-Contact (DIEC) program integrating interfaith information and intergroup contact, or a Control program involving within-faith information and ingroup contact. Participants also completed pre- and post-program measures of intergroup bias. Using Linguistic Inquiry and Word Count (LIWC), a computerised text analysis program, we objectively analysed data from across the eight Internet sessions, and found that groups in the two conditions expressed emotions differently. That is, the DIEC chat groups used more affect and positive emotion words, and less anger and sadness words than the Control chat groups. Mediation analyses showed that anger and sadness mediated the intervention effect on T2, T3 and T4 intergroup bias. In other words, DIEC chat groups' reduced expressions of anger and sadness were related to reduced short- and long-term intergroup bias. These findings highlight the significant role that structured Internet interactions can play in creating positive and long-lasting intergroup relations.